2017
DOI: 10.21608/ajs.2017.13620
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Some Egyptian Plant Extracts for Biological Activity Against Some Pathogenic Bacteria

Abstract: Plants and plant by-products are now gaining attractiveness in treatment of bacterial infections and food preservation. The objective of this study was to assess antibacterial activity of some Egyptian plant and plant by-products against the locally pathogenic isolates from patients having infectious diseases in our country. Screening of antibacterial activity of ethanol, methanol and hexane extracts of some plants: grape leaves (Vitis vinifera), mulberry leaves (Morus alba), mallow leaves (Corchorus olitorius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Black mulberry (Morus nigra L.), which originates from China, is cultivated for its fruits in Southern Europe and Southwest Asia (Mosayebi & Tabatabaei Yazdi, 2018). Mulberry fruits and leaf wastes have been widely studied (Abdel-Hamid et al, 2017;Huang et al, 2011;Koyuncu, 2004;Li et al, 2017;Mena et al, 2016;Natić et al, 2015;Okatan, 2018;Raman et al, 2016;Zhang et al, 2018); however, mulberry seeds have been underexploited, compared to grape pomace and seeds. A substantial amount of mulberry fruits is processed into juice and juice concentrates, indeed the mulberry production in Turkey exceeded 74 thousand tons (Tomas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Black mulberry (Morus nigra L.), which originates from China, is cultivated for its fruits in Southern Europe and Southwest Asia (Mosayebi & Tabatabaei Yazdi, 2018). Mulberry fruits and leaf wastes have been widely studied (Abdel-Hamid et al, 2017;Huang et al, 2011;Koyuncu, 2004;Li et al, 2017;Mena et al, 2016;Natić et al, 2015;Okatan, 2018;Raman et al, 2016;Zhang et al, 2018); however, mulberry seeds have been underexploited, compared to grape pomace and seeds. A substantial amount of mulberry fruits is processed into juice and juice concentrates, indeed the mulberry production in Turkey exceeded 74 thousand tons (Tomas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Abdel-Hamid et al (2017) revealed the antibacterial properties of grape and mulberry leaf extracts against Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella typhimurium. Additionally, Huang et al (2011) suggested that anthocyanins from mulberry fruits might be used to prevent gastric carcinoma formation and Peixoto et al (2018) described Vitis vinifera L. seed winery wastes as potential cytotoxic agents against MCF-7 breast adenocarcinoma and HeLa cervical carcinoma tumour cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mulberry also has economic importance for the sericulture industry, as it is traditionally used to feed silkworms in Asia (Lamberti et al, 2019). Previous studies have demonstrated several medicinal properties of mulberry plants, including antihyperglycemic (Chen et al, 2018), antioxidant (Polumackanycz et al, 2019) and antibacterial (Abdel-Hamid et al, 2017) activities. Extracts of M. alba L. leaves have also shown beneficial effects against bacteria isolated from humans, such as S. aureus and E. coli (minimum inhibitory concentration [MIC] 0.32 mg/mL and minimum bactericidal concentration [MBC] 0.64 mg/mL) (Abdel-Hamid et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated several medicinal properties of mulberry plants, including antihyperglycemic (Chen et al, 2018), antioxidant (Polumackanycz et al, 2019) and antibacterial (Abdel-Hamid et al, 2017) activities. Extracts of M. alba L. leaves have also shown beneficial effects against bacteria isolated from humans, such as S. aureus and E. coli (minimum inhibitory concentration [MIC] 0.32 mg/mL and minimum bactericidal concentration [MBC] 0.64 mg/mL) (Abdel-Hamid et al, 2017). A study of leaf extracts from two Morus species (M. alba and M. rubra L.) showed effects against gram-negative and gram-positive bacterial ATCC strains, including S. aureus, S. epidermidis, S. pyogenes, E. faecalis, Propionibacterium acnes, E. coli, P. aeruginosa, Acinetobacter baumannii, Proteus mirabilis, and K. pneumoniae, with MIC and MBC values of 15.75-252.00 mg/mL (Miljkovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%